Kashf al-Gharā’ib: Terjemahan atas Kitab Munfarijah Karya Imām Muḥaqqiq Abī Yaḥyā Zayn al-Dīn Zakarīyā - Syaukani Syaukani (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2017)
An effort to preserve and utilize manuscripts in this archipelago, especially religious manuscripts, is very important due to, at least two reasons. Firstly, there has been abundant important information pertinent to religious phenomena in the manuscripts. Secondly, the physical condition of the manuscripts has been increasingly fragile. Following the process of choosing the manuscript, the author has selected one of the manuscripts preserved in the State Museum of North Sumatra. This study employs the theory of philology, literature, and history in analyzing the manuscript. Analyses are focused on the language used, the cultural background of the manuscript, and the region’s social history where it has been written. The findings of this study tell us that the manuscript, named Kashf al-Gharā’ib, is a classical Islamic manuscript that still has been well preserved at the State Museum of North Sumatra. It contains the scientific information of fiqh (Islamic law), especially discussing the way of worshipping God. The manuscript also consists of religious poems and problems of adab (ethics). Of the three topics discussed in this manuscript, I give considerable attention to worship and ethical issues.